UKM PRAMESTI MALIMA ENERGI BANGKIT MENUJU NEW NORMAL - Alfrid Sentosa; Aston Pakpahan (Politeknik Negeri Sriwijaya, 2022)
UKM Pramesti Malima Energi (PMEFS) is an UKM that is engaged in fisheries, a variety of processed products, namely sarai abon abon, fish jerky, fish pentel, fish nuggets. PMEFS also felt the impact due to the Corona Virus pandemic, namely a decrease in turnover, none of the products sold were selling because buyers did not dare to leave the house, tourists were not there, shops where they put processed products were closed. Two periods run by UKM suffered losses in the first period in September and there was still half of the products in December that had not been sold. Tried another second production In December, the production carried out in December was of great concern because it suffered a very large loss. The products sold had to be recalled because they did not sell well in the market due to the closing of souvenir shops due to the implementation of the PSBB. The group also has a production house that is separate from the house, and its own gallery. Sales are also carried out in the gallery, through online (Facebook, Instagram, WhatsApp Business and Shopee. The priority problems of partners at this time are 1) Marketing, marketing during the pandemic season has decreased drastically, resulting in no return of production costs and no profit (loss). 2) consumer confidence in the health of the market is still low. The solution in solving the problem is for marketing: 1) making SOP in dealing with, available SOP, 2) making catalogs, catalogs available, 3) helping market via online by advertising on social media, advertising installed on social media, 4) promoting by buy 2 get 1 free, promotions and products sell. From several solutions and targets, we have the belief that this can restore the condition of UKM to the same as before this pandemic period hit. In terms of increased sales targets, it can be seen from the number of orders that come in, shoppe accounts that give an asterisk increase.